Characterization of ovarian follicular development and steroid profile during estrous cycle and seasonal anestrous in buffalo - SARATH, T; SINGH, S K; ARUNMOZHI, N; RAJKUMAR, R; SAXENA, A; AGARWAL, S K (The Indian Journal of Animal Sciences, 2016)
The experiment was conducted to study ovarian follicular population, its diameter, steroid profile (estradiol 17ß and progesterone) and corpus luteum development during estrous cycle and seasonal anestrous in Murrah buffaloes. They were categorized into 2 groups based on the estrus signs i.e. cyclic (6) and anestrous (6) and subjected to ultrasound scanning of ovaries on day 0 (day of estrus in cyclic and day of first scanning in anestrous buffaloes), 6, 10 and 16 using B-mode scanner equipped with 6.0 MHz linear array transducer. Blood samples were collected on the above days for the estimation of the progesterone and estradiol-17ß. The mean number of small follicles on day 0 and 10 and medium follicles on day 10 were significantly higher within as well as between the cyclic and anestrous buffaloes, while mean number of large follicles on day 0, 10 and 16 were significantly higher in the cyclic as compared to anestrous buffaloes. However, mean number of total follicles were significantly higher in cyclic as compared to anestrous buffaloes on all the days of scanning. The maximum diameter of large follicle was observed in cyclic buffaloes on day 0 (1.40±0.49 cm). The diameter of CL increased with its development and reached to its peak on day 10 (1.39±0.04 cm), thereafter, it reduced on day 16 (0.72±0.30 cm) of the cycle. The mean serum progesterone concentration was significantly higher on day 6, 10 and 16 than day 0 of the estrous cycle indicating development of functional corpus luteum, however, mean serum estradiol-17ß concentration was significantly higher on day 0 than the other days of cycle signifying follicular growth and development secreting higher amount of estrogen.